Preparation method of particle decoration electrostatic spinning anticorrosive coating with corrosion early warning and self-repairing functions
Self -warning and self -repairing materials are loaded in nano fibers through static spinning technology, combining epoxy resin to form a composite coating, solving the problem of static spinning coatings that lack corrosion warning and self -repair function in existing technology. The long -term protection and low maintenance costs of coating are realized.
Patent Information
- Application Number
- CN202411328073.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-28
AI Technical Summary
Existing electrospinning anticorrosion coatings lack products that have both corrosion warning and self-repair functions, and face the challenges of cost control, environmental adaptability and long-term stability in practical applications.
Adopt the granular nuclear shell nano fiber synthesis technology, which loads self -alert materials and self -repair materials through electrostatic spinning synthesis methods to form a composite coating and mix with epoxy resin to prepare a corrosion warning and self -cultivation function. Anticorrosive coating.
The self -warning and self -repair function of the coating can be realized. It can send signals in the early stage of corrosion and automatically restore the anticorrosive performance, significantly extend the protection cycle, and reduce maintenance costs.
Smart Images

Figure CN119372924A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing an electrostatic spinning anti-corrosion coating with both corrosion early warning and self-repairing functions, and belongs to the intersecting field of nanofibers, functional coating materials and anti-corrosion technology. Background Art
[0002] In many industrial fields, corrosion has always been an important factor affecting equipment life, increasing maintenance costs and causing safety hazards. Especially in the fields of petrochemicals, marine engineering, bridge construction, and aerospace, the corrosion of metal materials is particularly prominent. Although traditional anti-corrosion measures, such as coating protection and electrochemical protection, can delay the corrosion process to a certain extent, they often have shortcomings such as limited protection effect, short service life, and the need for regular inspection and maintenance. Therefore, the development of new anti-corrosion materials that are highly efficient, long-life, and have intelligent protection characteristics has become a hot topic in current research.
[0003] As an advanced material preparation method, electrospinning technology is widely used in many fields because it can produce nanofiber membranes with high specific surface area and porous structure. In recent years, researchers have begun to explore the application of electrospinning technology in the preparation of anti-corrosion coatings, aiming to improve the adhesion, corrosion resistance and self-healing ability of the coating by regulating the microstructure and composition of the fiber.
[0004] In the research of electrospinning anti-corrosion coatings, a key point is to introduce intelligent materials with early warning functions, such as conductive polymers, fluorescent materials or sensor materials, so that the coating can send out signals at the early stage of corrosion, and timely remind intervention to avoid further deterioration of corrosion. At the same time, the realization of self-repair function usually relies on strategies such as microcapsule technology, dynamic covalent bonds or shape memory materials, so that the coating can automatically restore its integrity and anti-corrosion performance after damage, significantly extending the protection period and reducing maintenance costs.
[0005] However, there are still few electrospinning anti-corrosion coating products on the market that have both early warning and self-repairing functions, and they face challenges in cost control, environmental adaptability and long-term stability in practical applications. Therefore, developing an electrospinning anti-corrosion coating that can effectively warn of corrosion and has self-repairing capabilities is of great significance for promoting technological progress in related industries and ensuring the safe operation of infrastructure. Summary of the invention
[0006] The technical task of the present invention is to address the deficiencies of the prior art and provide a method for preparing a particle-decorated electrostatic spinning anti-corrosion coating with both corrosion warning and self-repairing functions.
[0007] The technical solution adopted by the present invention to solve its technical problem is: 1. A method for preparing a particle-decorated electrospinning anti-corrosion coating with both corrosion warning and self-repairing functions, characterized in that it comprises a shell structure and a core structure coated inside the shell structure, and the specific implementation steps are as follows: 1) The specific sequence of particle-decorated core-shell nanofiber synthesis is: 1.1) Synthesis of shell solution: Weigh the polymer shell material, polymer spinning aid, and shell material solvent in a mass ratio of 1:0.1-1:5-15. The specific order of addition is: 1.1.1) Prepare the shell material solvent first, select one or more solvents and mix them in a mass ratio of 1:1-4, stir at a speed of 300-1000rpm for 2-4 hours at a temperature range of 20-40℃; 1.1.2) Then, weigh the polymer shell material and the spinning aid according to a mass ratio of 1:0.1-1, and then dissolve them in the shell material solvent according to a mass ratio of 1.1:5-15, and stir at a temperature range of 40-90°C and a speed of 300-2000rpm for 2-48 hours; 1.2) Preparation of core solution: weigh the core material and the core material solvent in a mass ratio of 1:5-10, stir at a speed of 300-1000 rpm for 2-6 hours at a temperature range of 40-90°C; 1.2.1) Prepare the core material solvent first, prepare 10-20wt.% polyvinyl pyrrolidone (PVP) solution, dissolve PVP in N, N-dimethylformamide (DMF), stir at 300-1000rmp for 2-6 hours at a temperature range of 40-90℃; 1.2.2) Weigh the early warning material and corrosion inhibitor in a mass ratio of 1:3-5; 1.2.3) Weigh the core material and the core material solvent in a mass ratio of 1:5-10, stir at a speed of 600-3000 rpm for 2-4 hours in a temperature range of 40-90°C; 1.3) Electrospinning synthesis: Fix the tin foil on the drum receiver, load the shell solution and core solution into a 5-20mL syringe, install it on the spinning machine, turn on the power, adjust the parameters, and perform electrospinning synthesis. The specific steps are as follows: 1.3.1) First, set the front dead point of the push device to zero, use a syringe capacity of 5-20mL, set the negative voltage to 2-4kV, the positive voltage to 8-25kV, the shell solution push rate to 0.01-3mm / min, the core solution push rate to 0.01-3mm / min, the receiving rate to 10-80r / min, the translation speed to 5-50mm / min, and the receiving distance to 5-30cm; 1.3.2) After spinning for 2 hours, the desired particle-decorated core-shell electrospinning material can be obtained; 2) Epoxy resin synthesis: Weigh epoxy resin monomer, curing agent, and diluent in a mass ratio of 1:0.2-1:0.2-1.5. The order of adding the drugs is: 2.1) Add epoxy resin monomer and curing agent into the beaker containing the magnet in sequence, heat the system to 25-60°C in a nitrogen atmosphere, and stir at 300-600 rpm for 30 minutes; 2.2) Add epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.2-1:0.2-1.5, and add diluent (n-butanol: xylene = 3:7) dropwise into the beaker, keep the temperature and speed constant, and stir for 20 minutes; 3) Preparation of early warning self-repairing anti-corrosion coating: The above-synthesized electrospinning material is mixed with epoxy resin in a thickness ratio of 0.1-0.5:1, coated on the surface of the substrate, and dried at room temperature for 12-48 hours to obtain an early warning self-repairing coating.
[0008] Optionally, the polymer shell material is any one of polycaprolactone, cellulose, chitosan, polyvinylidene fluoride, and polyacrylonitrile.
[0009] Optionally, the polymer spinning aid is any one of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone and polyethylene oxide.
[0010] Optionally, the solvent is any one or more of N,N-dimethylformamide, acetone, and polyvinyl pyrrolidone.
[0011] Optionally, the self-warning material is any one of rhodamine B, fluorescein, and crystal violet lactone.
[0012] Optionally, the corrosion inhibitor is any one of benzotriazole, 2-mercaptobenzothiazole, and 8-hydroxyquinoline.
[0013] Optionally, the epoxy resin monomer is any one or more of glycidyl ether epoxy resin including bisphenol A, bisphenol F, bisphenol S, glycidyl ester epoxy resin, glycidyl amine epoxy resin, and alicyclic epoxy resin.
[0014] Optionally, the epoxy resin curing agent is any one or more of a polyamide curing agent, anhydride curing agent, isocyanate curing agent, and amine curing agent.
[0015] The optional epoxy diluent is any one or more of n-butanol, acetone, ethanol, toluene, dimethylformamide, styrene, toluene and xylene.
[0016] The present invention provides a method for preparing a particle-decorated electrospinning anti-corrosion coating with both corrosion warning and self-repairing functions, and compared with the prior art, the beneficial effects produced are: 1. Integrated intelligent coating with self-warning and self-repairing functions based on core-shell nanofibers: Self-warning agents and self-repairing agents are loaded into nanofibers to prepare integrated intelligent coating with self-warning and self-repairing functions.
[0017] 2. The particle-decorated electrospun nanofibers synthesized in the present invention form a composite coating with epoxy resin. Since the nanofibers have excellent fluidity, they can achieve multiple self-repairs, solving the problem that the coating cannot provide long-term protection. It has broad application prospects and market value in future marine anti-corrosion coatings.
[0018] 3. This dual-functional integrated intelligent coating can be applied to a variety of metals, can exert self-repairing and anti-corrosion properties for a long time, and has self-warning and self-repairing functions for damage caused by fatigue cracking of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Attached Figure 1 This is a scanning electron microscope photograph of PVDF@CVL / 8-HQ synthesized in Example 1 of the present invention.
[0020] Attached Figure 2 This is the FT-IR spectrum of PVDF@CVL / 8-HQ synthesized in Example 1 of the present invention.
[0021] Attached Figure 3 It is P synthesized in Example 2 of the present invention. PVDF Nyquist comparison diagram of CH-30% anti-corrosion coating and blank coating.
[0022] Attached Figure 4 is P prepared in Example 3 of the present invention PVA Nyquist contrast of CCH-40% coating in 3.5wt.% sodium chloride solution after scratching for 1 day.
[0023] Attached Figure 5 is P prepared in Example 4 of the present invention PVDF SEM image of the cross section of the CB-40% coating.
[0024] Attached Figure 6 is the P prepared by implementing the fourth embodiment of the present invention PVDF Fluorescence occurrence at the scratch of CB-40% coating and blank coating without nanofibers added.
[0025] Attached Figure 7 is the P prepared in accordance with the fifth embodiment of the present invention PVB Nyquist plot of CH-40% coating after 30 days. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The present invention provides a particle-decorated electrostatically spun anti-corrosion coating with both corrosion warning and self-repairing functions. The coating is formed by mixing electrostatically spun nanofibers and epoxy resin in a thickness ratio of 0.1-0.5:1. The specific implementation steps are as follows: 1) The specific sequence of particle-decorated core-shell nanofiber synthesis is: 1.1) Synthesis of shell solution: Weigh the polymer shell material, polymer spinning aid, and shell material solvent in a mass ratio of 1:0.1-1:5-15. The specific order of addition is: 1.1.1) Prepare the shell material solvent first, select one or more solvents and mix them in a mass ratio of 1:1-4, stir at a speed of 300-1000rpm for 2-4 hours at a temperature range of 20-40℃; 1.1.2) Then, weigh the polymer shell material and the spinning aid according to a mass ratio of 1:0.1-1, and then dissolve them in the shell material solvent according to a mass ratio of 1.1:5-15, and stir at a temperature range of 40-90°C and a speed of 300-2000rpm for 2-48 hours; 1.2) Preparation of core solution: weigh the core material and the core material solvent in a mass ratio of 1:5-10, stir at a speed of 300-1000 rpm for 2-6 hours at a temperature range of 40-90°C; 1.2.1) Prepare the core material solvent first, prepare 10-20wt.% polyvinyl pyrrolidone (PVP) solution, dissolve PVP in N, N-dimethylformamide (DMF), stir at 300-1000rmp for 2-6 hours at a temperature range of 40-90℃; 1.2.2) Weigh the early warning material and corrosion inhibitor in a mass ratio of 1:3-5; 1.2.3) Weigh the core material and the core material solvent in a mass ratio of 1:5-10, stir at a speed of 600-3000 rpm for 2-4 hours in a temperature range of 40-90°C; 1.3) Electrospinning synthesis: Fix the tin foil on the drum receiver, load the shell solution and core solution into a 5-20mL syringe, install it on the spinning machine, turn on the power, adjust the parameters, and perform electrospinning synthesis. The specific steps are as follows: 1.3.1) First, set the front dead point of the push device to zero, use a syringe capacity of 5-20mL, set the negative voltage to 2-4kV, the positive voltage to 8-25kV, the shell solution push rate to 0.01-3mm / min, the core solution push rate to 0.01-3mm / min, the receiving rate to 10-80r / min, the translation speed to 5-50mm / min, and the receiving distance to 5-30cm; 1.3.2) After spinning for 2 hours, the desired particle-decorated core-shell electrospinning material can be obtained; 2) Epoxy resin synthesis: Weigh epoxy resin monomer, curing agent, and diluent in a mass ratio of 1:0.2-1:0.2-1.5. The order of adding the drugs is: 2.1) Add epoxy resin monomer and curing agent into the beaker containing the magnet in sequence, heat the system to 25-60°C in a nitrogen atmosphere, and stir at 300-600 rpm for 30 minutes; 2.2) Add epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.2-1:0.2-1.5, and add diluent (n-butanol: xylene = 3:7) dropwise into the beaker, keep the temperature and speed constant, and stir for 20 minutes; 3) Preparation of early warning self-repairing anti-corrosion coating: The above-synthesized electrospinning material is mixed with epoxy resin in a thickness ratio of 0.1-0.5:1, coated on the surface of the substrate, and dried at room temperature for 12-48 hours to obtain an early warning self-repairing coating.
[0028] The polymer shell material in step 1) is any one of polycaprolactone, cellulose, chitosan, polyvinylidene fluoride and polyacrylonitrile.
[0029] The polymer spinning aid in step 1) is any one of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone and polyethylene oxide.
[0030] The solvent in step 1) is any one or more of N,N-dimethylformamide, acetone, and polyvinyl pyrrolidone.
[0031] The self-warning material in step 1) is any one of rhodamine B, fluorescein, and crystal violet lactone.
[0032] The corrosion inhibitor in step 1) is any one of benzotriazole, 2-mercaptobenzothiazole and 8-hydroxyquinoline.
[0033] The epoxy resin monomer in step 2) is any one or more of glycidyl ether epoxy resins including bisphenol A, bisphenol F, bisphenol S, glycidyl ester epoxy resins, glycidyl amine epoxy resins, and alicyclic epoxy resins.
[0034] The epoxy resin curing agent in step 2) is any one or more of a polyamide curing agent, anhydride curing agent, isocyanate curing agent, and amine curing agent.
[0035] The epoxy diluent in step 2) is any one or more of n-butanol, acetone, ethanol, toluene, dimethylformamide, styrene, toluene and xylene. Embodiment 1
[0036] The present invention provides a particle-decorated electrostatically spun anti-corrosion coating with both corrosion warning and self-repairing functions. The coating is formed by mixing electrostatically spun nanofibers and epoxy resin. The specific steps are as follows: 1) The specific sequence of particle-decorated core-shell nanofiber synthesis is: 1.1) Synthesis of shell solution: Weigh the polymer shell material, polymer spinning aid, and shell material solvent in a mass ratio of 1:0.3:10. The specific order of addition is: 1.1.1) Prepare the shell material solvent by mixing acetone and N,N-dimethylformamide (DMF) in a mass ratio of 1:4, stirring at 400 rpm for 2 hours at a temperature range of 30°C; 1.1.2) Then, polyvinylidene fluoride (PVDF) and polyethylene glycol (PEG) were weighed in a mass ratio of 1:0.3, and then dissolved in a shell material solvent in a mass ratio of 1.3:10, and stirred at a speed of 400 rpm for 12 hours at a temperature range of 60°C; 1.2) Preparation of core solution: weigh the core material and the core material solvent in a mass ratio of 1:7, stir at a speed of 500 rpm for 4 hours at a temperature range of 40°C; 1.2.1) Prepare the core material solvent first, prepare 10wt.% polyvinyl pyrrolidone (PVP) solution, dissolve PVP in DMF, stir at 500rmp for 5 hours at a temperature range of 60℃; 1.2.2) Weigh crystal violet lactone (CVL) and 8-hydroxyquinoline (8-HQ) in a mass ratio of 1:4; 1.2.3) Weigh the core material and the core material solvent in a mass ratio of 1:7, stir at a speed of 600 rpm for 3 hours within a temperature range of 50°C; 1.3) Electrospinning synthesis: Fix the tin foil on the drum receiver, load the shell solution and core solution into a 10mL syringe, install it on the spinning machine, turn on the power, adjust the parameters, and perform electrospinning synthesis. The specific steps are as follows: 1.3.1) First, set the front dead point of the push device to zero, use a syringe capacity of 10 mL, set the negative voltage to 3 kV, the positive voltage to 15 kV, the shell solution push rate to 0.2 mm / min, the core solution push rate to 0.05 mm / min, the receiving rate to 80 r / min, the translation speed to 40 mm / min, and the receiving distance to 20 cm; 1.3.2) After spinning for 2 hours, the desired particle-decorated core-shell electrospinning material (PVDF@CVL / 8-HQ) can be obtained; 2) Epoxy resin synthesis: Weigh epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5. The order of adding the drugs is: 2.1) Add bisphenol A epoxy resin and polyamide curing agent into the beaker containing the magnet in sequence, heat the system to 40°C in a nitrogen atmosphere, and stir at 400 rpm for 30 minutes; 2.2) Add epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5, and add diluent (n-butanol: xylene = 3:7) dropwise into the beaker, keep the temperature and speed constant, and stir for 20 minutes; 3) Preparation of early warning self-healing anti-corrosion coating: The above-synthesized electrospinning material (PVDF@CVL / 8-HQ) was mixed with epoxy resin at a thickness ratio of 0.4:1, coated on the substrate surface, and dried at room temperature for 24 hours to obtain an early warning self-healing coating named PCH-40%.
[0037] The performance of the electrospun nanofibers obtained above was tested: The scanning electron microscope image of the synthesized PVDF@CVL / 8-HQ is shown in Figure 1 As shown, the nanofibers present an intricate, densely interwoven network structure, and the material inside such a structure has extremely high fluidity.
[0038] The FT-IR spectrum of PVDF@CVL / 8-HQ nanofibers is shown in Figure 2 As shown, the C=O vibration (1748 cm -1 ), and 8-HQ at 1280 cm -1 The characteristic absorption peaks, corresponding to the CN stretching vibration and CH bending vibration, confirmed the successful loading of CVL and 8-HQ into PVDF nanofibers. Embodiment 2
[0039] The present invention provides a particle-decorated electrostatically spun anti-corrosion coating with both corrosion warning and self-repairing functions. The coating is formed by mixing electrostatically spun nanofibers and epoxy resin. The specific steps are as follows: 1) The specific sequence of particle-decorated core-shell nanofiber synthesis is: 1.1) Synthesis of shell solution: Weigh the polymer shell material, polymer spinning aid, and shell material solvent in a mass ratio of 1:0.4:10. The specific order of addition is: 1.1.1) Prepare the shell material solvent by mixing acetone and N,N-dimethylformamide (DMF) in a mass ratio of 1:4, stirring at 500 rpm for 2 hours at a temperature range of 40°C; 1.1.2) Then, polyvinylidene fluoride (PVDF) and polyethylene glycol (PEG) were weighed in a mass ratio of 1:0.4, and then dissolved in a shell material solvent in a mass ratio of 1.4:10, and stirred at a speed of 500 rpm for 12 hours at a temperature range of 65°C; 1.2) Preparation of core solution: weigh the core material and the core material solvent in a mass ratio of 1:8, stir at a speed of 500 rpm for 4 hours at a temperature range of 50°C; 1.2.1) Prepare the core material solvent first, prepare 15wt.% polyvinyl pyrrolidone (PVP) solution, dissolve PVP in DMF, stir at 500rmp for 5 hours at a temperature range of 60℃; 1.2.2) Weigh crystal violet lactone (CVL) and 8-hydroxyquinoline (8-HQ) in a mass ratio of 1:4; 1.2.3) Weigh the core material and the core material solvent in a mass ratio of 1:7, stir at a speed of 600 rpm for 3 hours within a temperature range of 50°C; 1.3) Electrospinning synthesis: Fix the tin foil on the drum receiver, load the shell solution and core solution into a 10mL syringe, install it on the spinning machine, turn on the power, adjust the parameters, and perform electrospinning synthesis. The specific steps are as follows: 1.3.1) First, set the front dead point of the push device to zero, use a syringe capacity of 10 mL, set the negative voltage to 3 kV, the positive voltage to 15 kV, the shell solution push rate to 0.2 mm / min, the core solution push rate to 0.05 mm / min, the receiving rate to 80 r / min, the translation speed to 40 mm / min, and the receiving distance to 20 cm; 1.3.2) After spinning for 2 hours, the desired particle-decorated core-shell electrospinning material (PVDF@CVL / 8-HQ) can be obtained; 2) Epoxy resin synthesis: Weigh epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5. The order of adding the drugs is: 2.1) Add bisphenol A epoxy resin and ethylenediamine curing agent into the beaker containing the magnet in sequence, heat the system to 40°C in a nitrogen atmosphere, and stir at 400 rpm for 30 minutes; 2.2) Add epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5, and add diluent (n-butanol: xylene = 3:7) dropwise into the beaker, keep the temperature and speed constant, and stir for 20 minutes; 3) Preparation of early warning self-repairing anti-corrosion coating: The above-synthesized electrospinning material and epoxy resin were mixed in a thickness ratio of 0.3:1, coated on the substrate surface, and dried at room temperature for 24 hours to obtain an early warning self-repairing coating named P PVDF CH - 30%.
[0040] The performance test of the above-mentioned self-repairing coating with early warning was carried out: Prepared P PVDF Nyquist comparison of CH-30% anti-corrosion coating and blank coating in 3.5wt.% sodium chloride solution, such as Figure 3 It can be seen that the coating prepared in this embodiment has good corrosion resistance. Embodiment 3
[0041] The present invention provides a particle-decorated electrostatically spun anti-corrosion coating with both corrosion warning and self-repairing functions. The coating is formed by mixing electrostatically spun nanofibers and epoxy resin. The specific steps are as follows: 1) The specific sequence of particle-decorated core-shell nanofiber synthesis is: 1.1) Synthesis of shell solution: Weigh the polymer shell material, polymer spinning aid, and shell material solvent in a mass ratio of 1:0.4:10. The specific order of addition is: 1.1.1) Prepare the shell material first, prepare a 2% (W / V) chitosan solution, dissolve 4g chitosan powder in 190mL of 2% acetic acid aqueous solution, stir at 500rpm for 4 hours at a temperature range of 30°C. At the same time, prepare a 15wt.% polyvinyl alcohol (PVA) aqueous solution. Dissolve the polyvinyl alcohol (PVA) powder in deionized water and heat it in a water bath at 95°C for 24 hours to obtain a 15wt.% PVA aqueous solution; 1.1.2) Then, chitosan (CS) solution and polyvinyl alcohol (PVA) solution were weighed and mixed in a mass ratio of 1:0.4, and stirred at 500 rpm for 12 hours at a temperature range of 65°C; 1.2) Preparation of core solution: weigh the core material and the core material solvent in a mass ratio of 1:8, stir at a speed of 500 rpm for 4 hours at a temperature range of 40°C; 1.2.1) Prepare the core material solvent first, prepare 15wt.% polyvinyl pyrrolidone (PVP) solution, dissolve PVP in DMF, stir at 500rmp for 5 hours at a temperature range of 60℃; 1.2.2) Weigh crystal violet lactone (CVL) and 8-hydroxyquinoline (8-HQ) in a mass ratio of 1:4; 1.2.3) Weigh the core material and the core material solvent in a mass ratio of 1:7, stir at a speed of 600 rpm for 3 hours within a temperature range of 50°C; 1.3) Electrospinning synthesis: Fix the tin foil on the drum receiver, load the shell solution and core solution into a 10mL syringe, install it on the spinning machine, turn on the power, adjust the parameters, and perform electrospinning synthesis. The specific steps are as follows: 1.3.1) First, set the front dead point of the push device to zero, use a syringe capacity of 10 mL, set the negative voltage to 3 kV, the positive voltage to 15 kV, the shell solution push rate to 0.2 mm / min, the core solution push rate to 0.05 mm / min, the receiving rate to 80 r / min, the translation speed to 40 mm / min, and the receiving distance to 20 cm; 1.3.2) After spinning for 2 hours, the desired particle-decorated core-shell electrospinning material (PVA / CS@CVL / 8-HQ) can be obtained; 2) Epoxy resin synthesis: Weigh epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5. The order of adding the drugs is: 2.1) Add bisphenol A epoxy resin and polyamide curing agent into the beaker containing the magnet in sequence, heat the system to 40°C in a nitrogen atmosphere, and stir at 400 rpm for 30 minutes; 2.2) Add epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5, and add diluent (n-butanol: xylene = 3:7) dropwise into the beaker, keep the temperature and speed constant, and stir for 20 minutes; 3) Preparation of early warning self-repairing anti-corrosion coating: The above-synthesized electrospinning material and epoxy resin were mixed in a thickness ratio of 0.4:1, coated on the substrate surface, and dried at room temperature for 24 hours to obtain an early warning self-repairing coating named P PVA CCH-40%.
[0042] The performance test of the above-mentioned self-repairing coating with early warning was carried out: Prepared P PVA The impedance comparison of CCH-40% coating in 3.5wt.% sodium chloride solution after scratching for 1 day. Figure 4 It can be seen that the coating prepared in this embodiment has good corrosion resistance. Embodiment 4
[0043] The present invention provides a particle-decorated electrostatically spun anti-corrosion coating with both corrosion warning and self-repairing functions. The coating is formed by mixing electrostatically spun nanofibers and epoxy resin. The specific steps are as follows: 1) The specific sequence of particle-decorated core-shell nanofiber synthesis is: 1.1) Synthesis of shell solution: Weigh the polymer shell material, polymer spinning aid, and shell material solvent in a mass ratio of 1:0.3:10. The specific order of addition is: 1.1.1) Prepare the shell material solvent by mixing acetone and N,N-dimethylformamide (DMF) in a mass ratio of 1:4, stirring at 400 rpm for 2 hours at a temperature range of 30°C; 1.1.2) Then, polyvinylidene fluoride (PVDF) and polyethylene glycol (PEG) were weighed in a mass ratio of 1:0.3, and then dissolved in a shell material solvent in a mass ratio of 1.3:10, and stirred at a speed of 400 rpm for 24 hours at a temperature range of 70°C; 1.2) Preparation of core solution: weigh the core material and the core material solvent in a mass ratio of 1:7, stir at a speed of 500 rpm for 4 hours at a temperature range of 40°C; 1.2.1) Prepare the core material solvent first, prepare 15wt.% polyvinyl pyrrolidone (PVP) solution, dissolve PVP in DMF, stir at 500rmp for 5 hours at a temperature range of 60℃; 1.2.2) Weigh crystal violet lactone (CVL) and benzotriazole (BTA) in a mass ratio of 1:4; 1.2.3) Weigh the core material and the core material solvent in a mass ratio of 1:7, stir at a speed of 600 rpm for 3 hours within a temperature range of 50°C; 1.3) Electrospinning synthesis: Fix the tin foil on the drum receiver, load the shell solution and core solution into a 10mL syringe, install it on the spinning machine, turn on the power, adjust the parameters, and perform electrospinning synthesis. The specific steps are as follows: 1.3.1) First, set the front dead point of the push device to zero, use a syringe capacity of 10 mL, set the negative voltage to 3 kV, the positive voltage to 15 kV, the shell solution push rate to 0.2 mm / min, the core solution push rate to 0.05 mm / min, the receiving rate to 80 r / min, the translation speed to 40 mm / min, and the receiving distance to 20 cm; 1.3.2) After spinning for 2 hours, the desired particle-decorated core-shell electrospinning material (PVDF@CVL / BTA) can be obtained; 2) Epoxy resin synthesis: Weigh epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5. The order of adding the drugs is: 2.1) Add bisphenol A epoxy resin and polyamide curing agent into the beaker containing the magnet in sequence, heat the system to 40°C in a nitrogen atmosphere, and stir at 400 rpm for 30 minutes; 2.2) Add epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5, and add diluent (n-butanol: xylene = 3:7) dropwise into the beaker, keep the temperature and speed constant, and stir for 20 minutes; 3) Preparation of early warning self-healing anti-corrosion coating: The above-synthesized electrospinning material (PVDF@CVL / BTA) was mixed with epoxy resin at a thickness ratio of 0.4:1, coated on the substrate surface, and dried at room temperature for 24 hours to obtain an early warning self-healing coating named PCB-40%.
[0044] The performance test of the above-mentioned self-repairing coating with early warning was carried out: Prepared P PVDF SEM image of the cross section of the CB-40% coating, such as Figure 5 It can be seen that the distribution state of the nanofibers in the coating is uniformly and densely dispersed, forming a dense network structure. This distribution can improve the anti-corrosion performance of the coating.
[0045] Prepared P PVDF The fluorescence comparison of the scratches between the CB-40% warning coating and the blank coating without nanofibers is shown in Figure 2. Figure 6 It can be seen that the coating prepared in this embodiment has early warning capability. Embodiment 5
[0046] The present invention provides a particle-decorated electrostatically spun anti-corrosion coating with both corrosion warning and self-repairing functions. The coating is formed by mixing electrostatically spun nanofibers and epoxy resin. The specific steps are as follows: 1) The specific sequence of particle-decorated core-shell nanofiber synthesis is: 1.1) Synthesis of shell solution; 1.1.1) Prepare the shell material solvent by mixing ethanol and N,N-dimethylformamide (DMF) in a mass ratio of 1:1, stirring at 400 rpm for 2 hours at a temperature range of 30°C; 1.1.2) Then, the shell material PVB and the shell material solvent are mixed in a mass ratio of 1.5:10, and stirred at a speed of 400 rpm for 24 hours at a temperature range of 50°C; 1.2) Preparation of core solution: weigh the core material and the core material solvent in a mass ratio of 1:7, stir at a speed of 500 rpm for 4 hours at a temperature range of 40°C; 1.2.1) Prepare the core material solvent first, prepare 10wt.% polyvinyl pyrrolidone (PVP) solution, dissolve PVP in DMF, stir at 600 rpm for 6 hours at a temperature range of 65°C; 1.2.2) Weigh crystal violet lactone (CVL) and 8-hydroxyquinoline (8-HQ) in a mass ratio of 1:3; 1.2.3) Weigh the core material and the core material solvent in a mass ratio of 1:8, stir at a speed of 800 rpm for 4 hours within a temperature range of 60°C; 1.3) Electrospinning synthesis: Fix the tin foil on the drum receiver, load the shell solution and core solution into a 10mL syringe, install it on the spinning machine, turn on the power, adjust the parameters, and perform electrospinning synthesis. The specific steps are as follows: 1.3.1) First, set the front dead point of the push device to zero, use a syringe capacity of 10 mL, set the negative voltage to 3 kV, the positive voltage to 15 kV, the shell solution push rate to 0.2 mm / min, the core solution push rate to 0.05 mm / min, the receiving rate to 80 r / min, the translation speed to 40 mm / min, and the receiving distance to 20 cm; 1.3.2) After spinning for 2 hours, the desired particle-decorated core-shell electrospinning material (PVB@CVL / 8-HQ) can be obtained; 2) Epoxy resin synthesis: Weigh epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5. The order of adding the drugs is: 2.1) Add bisphenol A epoxy resin and polyamide curing agent into the beaker containing the magnet in sequence, heat the system to 40°C in a nitrogen atmosphere, and stir at 400 rpm for 30 minutes; 2.2) Add epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.5:1.5, and add diluent (n-butanol: xylene = 3:7) dropwise into the beaker, keep the temperature and speed constant, and stir for 20 minutes; 3) Preparation of early warning self-repairing anti-corrosion coating: The above-synthesized electrospinning material (PVB@CVL / 8-HQ) was mixed with epoxy resin at a thickness ratio of 0.4:1, coated on the substrate surface, and dried at room temperature for 24 hours to obtain an early warning self-repairing coating named P PVB CH - 40%.
[0047] The performance test of the above-mentioned self-repairing coating with early warning was carried out: Prepared P PVB Nyquist diagram of CH-40% coating within 30 days, as shown in Figure 7 It can be seen that the coating prepared in this embodiment has excellent anti-corrosion ability.
[0048] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the present application.
[0049] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
[0050] Except for the technical features described in the specification, all other technical features are known technologies to those skilled in the art.
Claims
1. A method for preparing a particle-decorated electrospinning anti-corrosion coating with both corrosion warning and self-repairing functions, characterized in that it comprises a shell structure and a core structure coated inside the shell structure, and the specific implementation steps are as follows: 1) The specific sequence of particle-decorated core-shell nanofiber synthesis is: 1.1) Synthesis of shell solution: Weigh the polymer shell material, polymer spinning aid, and shell material solvent in a mass ratio of 1:0.1-1:5-15. The specific order of addition is: 1.1.1) Prepare the shell material solvent first, select one or more solvents and mix them in a mass ratio of 1:1-4, stir at a speed of 300-1000rpm for 2-4 hours at a temperature range of 20-40℃; 1.1.2) Then, weigh the polymer shell material and the spinning aid according to a mass ratio of 1:0.1-1, and then dissolve them in the shell material solvent according to a mass ratio of 1.1:5-15, and stir at a temperature range of 40-90°C and a speed of 300-2000rpm for 2-48 hours; 1.2) Preparation of core solution: weigh the core material and the core material solvent in a mass ratio of 1:5-10, stir at a speed of 300-1000 rpm for 2-6 hours at a temperature range of 40-90°C; 1.2.1) Prepare the core material solvent first, prepare 10-20wt.% polyvinyl pyrrolidone (PVP) solution, dissolve PVP in N, N-dimethylformamide (DMF), stir at 300-1000rmp for 2-6 hours at a temperature range of 40-90℃; 1.2.2) Weigh the early warning material and corrosion inhibitor in a mass ratio of 1:3-5; 1.2.3) Weigh the core material and the core material solvent in a mass ratio of 1:5-10, stir at a speed of 600-3000 rpm for 2-4 hours in a temperature range of 40-90°C; 1.3) Electrospinning synthesis: Fix the tin foil on the drum receiver, load the shell solution and core solution into a 5-20mL syringe, install it on the spinning machine, turn on the power, adjust the parameters, and perform electrospinning synthesis. The specific steps are as follows: 1.3.1) First, set the front dead point of the push device to zero, use a syringe capacity of 5-20mL, set the negative voltage to 2-4kV, the positive voltage to 8-25kV, the shell solution push rate to 0.01-3mm / min, the core solution push rate to 0.01-3mm / min, the receiving rate to 10-80r / min, the translation speed to 5-50mm / min, and the receiving distance to 5-30cm; 1.3.2) After spinning for 2 hours, the desired particle-decorated core-shell electrospinning material can be obtained; 2) Epoxy resin synthesis: Weigh epoxy resin monomer, curing agent, and diluent in a mass ratio of 1:0.2-1:0.2-1.
5. The order of adding the drugs is: 2.1) Add epoxy resin monomer and curing agent to the beaker containing the magnet in sequence, heat the system to 25-60°C in a nitrogen atmosphere, and stir at 300-600 rpm for 30 minutes; 2.2) Add epoxy resin monomer, curing agent and diluent in a mass ratio of 1:0.2-1:0.2-1.5, and add diluent (n-butanol: xylene = 3:7) dropwise into the beaker, keep the temperature and speed constant, and stir for 20 minutes; 3) Preparation of early warning self-repairing anti-corrosion coating: The above-synthesized electrospinning material and epoxy resin are mixed in a thickness ratio of 0.1-0.5:1, coated on the surface of the substrate, and dried at room temperature for 12-48 hours to obtain an early warning self-repairing coating; The polymer shell material is any one of polycaprolactone, cellulose, chitosan, polyvinylidene fluoride, and polyacrylonitrile; the polymer spinning aid is any one of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, and polyethylene oxide; the solvent is any one or more of N,N-dimethylformamide, acetone, and polyvinyl pyrrolidone; the self-warning material is any one of rhodamine B, fluorescein, and crystal violet lactone; the corrosion inhibitor is any one of benzotriazole, 2-mercaptobenzothiazole, and 8-hydroxyquinoline.
2. The particle-decorated electrostatic spinning anti-corrosion coating with both corrosion warning and self-repairing functions according to claim 1, characterized in that: The epoxy resin comprises: Glycidyl ether epoxy resins include any one or more of bisphenol A type, bisphenol F type, bisphenol S type, glycidyl ester epoxy resins, glycidyl amine epoxy resins, and alicyclic epoxy resins; The epoxy resin curing agent is any one or more of a polyamide curing agent, anhydride curing agent, isocyanate curing agent, and amine curing agent; The epoxy diluent is selected from any one or more of n-butanol, acetone, ethanol, toluene, dimethylformamide, styrene, toluene and xylene.
3. Application of a particle-decorated electrostatic spinning anti-corrosion coating with both corrosion warning and self-repairing functions, characterized in that: The self-repairing anti-corrosion coating synthesized in claim 2 is applied to the metal substrate to be protected, cured at 60° C. for 48 hours, and cooled to ambient temperature to finally obtain a warning self-repairing organic coating having excellent self-repairing and anti-corrosion properties.
Citation Information
Cited By
Preparation method of titanium alloy anti-corrosion self-repairing intelligent coating used in marine environment
CN120005484A
Preparation method of noise-reducing and anti-corrosion multifunctional coating
CN120157950A
Nano modified polysiloxane heavy anti-corrosion coating and preparation method thereof
CN121045953A
Nanometer modified polysiloxane heavy-duty anticorrosive coating and preparation method thereof
CN121045953B
Flame-retardant smoke-suppression anticorrosive fiber material, coating and preparation method thereof
CN121826922A